Rancang Bangun Sistem Pembelajaran Online Berbasis Web Menggunakan Database MySQL - Muh.Arfah Wahlil Pratama; Abdillah Sirfanal Hak; Denis Pratama; Putri Yunansi Bonsa; Sriyanti Azzahrah; Novita Kunia Wahyu; Imelda Masdar; Kharisma Dewi; Tri Ulfani; Adel Asti Ananta (Plexi Digital Indonesia, 2026)
The rapid development of information technology has driven the transformation of conventional learning into web-based online learning. However, not all educational institutions have sufficient resources and infrastructure to adopt large-scale e-learning platforms. This study aims to design and develop a web-based online learning system using the PHP programming language and a MySQL database to support learning activities in small-scale higher education institutions. The research method employed is software engineering using the Waterfall development model, which includes requirements analysis, system design, implementation, and testing stages. The system involves three main actors: Administrator, Lecturer, and Student, with features for user management, learning material management, assignments, quizzes, and learning assessment. The results of functional testing using the black-box method indicate that all system features operate in accordance with user requirements. This study contributes a simple e-learning system model that is easy to develop and implement in educational institutions with limited technological infrastructure.